Pengaruh Content Marketing Instagram dan Performance Influencer Terhadap Customer Engagement di Istoria Cafe Kavling DPR Sidoarjo - Muslikha Irbah Zakiyah; Sholikhah, Afifatus; Lestari Dewi, Lailatul Ramadhani; Purwaningtyas, Esti; Pratama, Fredi Aldi; Aisa, Riska Dewi (Journal of Research and Publication Innovation, 2024)
The purpose of this article is to examine further the influence of Instagram content marketing and influencer performance on customer engagement at Istoria Cafe Kavling DPR Sidoarjo. This research method applies a quantitative approach through quantitative methods. The subjects of this research were Instagram users who visited the Istoria Café Kavling DPR Sidoarjo. The sampling mechanism uses a questionnaire survey method which is filled out online by respondents. Meanwhile, the data analysis technique used is multiple linear regression testing. The sample size in this study was 100 respondents. This research meets the criteria for validity and reliability. The processing uses SPPS version 18 software and uses multivariate linear regression. Based on the research results, it is known that the influence variables of Instagram content marketing (X1) and influencer performance (X2) have a significant influence on the level of customer engagement at the Istoria Field Cafe in DPR Sidoarjo (Y).